2013
DOI: 10.1371/journal.pone.0077601
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenicity and Cytokine Gene Expression Pattern of a Serotype 4 Fowl Adenovirus Isolate

Abstract: Hydropericardium-hepatitis syndrome (HHS), a recently emerged disease of chickens, is caused by some strains of fowl adenovirus serotype 4 (FAdV-4). In this study, a Canadian FAdV-4 isolate, designated as FAdV-4 ON1, was evaluated for pathogenicity after oral and intramuscular (im) infection of specific pathogen free (SPF) chickens. Pathogenicity was evaluated by observation of clinical signs and gross and histological lesions. The highest viral DNA copy numbers, irrespective of the inoculation route, were det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 37 publications
5
28
0
Order By: Relevance
“…In some studies, chickens were infected with FAdV-4 via IM, oral, or intranasal routes ( 17 , 36 38 ). When compared with the oral and intranasal routes, IM produces stronger pathogenicity ( 17 , 37 ). In duck AdV infection models, the IM infection route was often used ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…In some studies, chickens were infected with FAdV-4 via IM, oral, or intranasal routes ( 17 , 36 38 ). When compared with the oral and intranasal routes, IM produces stronger pathogenicity ( 17 , 37 ). In duck AdV infection models, the IM infection route was often used ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…So far, the whole genome sequences of FAdV-4 strains KR5 (Marek et al, 2012) and ON1 (Griffin & Nagy, 2011) have been reported, both of which are of low virulence (Cook, 1983;Grgic et al, 2013). However, it should be noted that during the preparation of this manuscript, the complete genome of a highly pathogenic FAdV-4 was reported (Zhao et al, 2015).…”
Section: Introductionmentioning
confidence: 94%
“…These genes are engaged in the interaction between FAdV and the host cell or host immune system [2,8]. Elucidation of the gene functions will facilitate the development of attenuated vaccines, which havethe advantages over inactivated or subunit vaccines of high efficacy, easy inoculation and low costs [24][25][26][27]. On the other hand, gene function study will help the construction of FAdV-based gene delivery tools.…”
Section: Discussionmentioning
confidence: 99%